Toxicidade aguda e rejeição ao fungicida oxicloreto de cobre para eisenia fetida e pontoscolex corethrurus (oligochaeta). - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
﻿With the advance of the technology in agriculture, diverse substances have been used for the control of pests. As the fungicides to the copper base (metal heavy), these if accumulate in the environment compromising the activity of the organisms, over all the earthworms, essentials to the maintenance of the chemical and biological processes. The objective of this study was to evaluate the effect of the fungicide cooper oxychloride on earthworms considering parameters mortality and rejection to the contaminate the soil. Two species, Eisenia fetida (standard test species) and Pontoscolex corethrurus (Amazonian native species) have been selected as indicators of soil contamination of. E. fetida created in laboratory, from samples acquired in Manaus and, P. corethrurus collected in ground natural. For exposition to the contaminante two types of soil had been used, Gleissolo and Argissolo. The tested substance contained 588 g/kg of the active ingredient cooper oxychloride -35% of metallic copper. The methodology for determination of the acute toxicity and the effect on the behavior of rejection was based on OECD and ISO international protocols. The toxicity tests consisted on a contaminated soil with increased concentrations of cooper oxychloride. The acute toxicity was evaluated by the medium lethal concentration (CL50) using a Probit analysis, followed by the generation of the dose-response curve. Differences between the control and treatments had been evaluated through the analysis of variance (ANOVA) and for comparison of averages used the Dunnett test was used with a 5% of significance. For the data of rejection to the substratum the t-Student test for comparison of the averages of the number of individuals between the contaminated sections and control. The esteem value of the CL50 after 14 days of exposition in the contaminated Gleissolo for E. fetida, was of 1162.3 mg Cu/kg (IC 95% of 975-1385.2), showing low lethality for this species. However, the native showed to greater sensitivity to copper, being the estimated value of CL50: 154.6 mg Cu/kg (58.9-405.7). In contrast to E. fetida the reduction of biomass in P. corethrurus was not significant in the Gleissolo acute test. However, for the Argissolo test it was observed a significant reduction for the concentration of 56. Due to the great variability of response for P. corethrurus in Argissolo, the data had not been adjusted in a typical dose-response curve, however the estimated CL50 in 84.3 mg Cu/kg (35-202.8). The rejection for the contaminated Gleissolo was observed for both the species, being that P. corethrurus showed to greater sensitivity to the copper that E. fetida with significant results at 14 and 28mg Cu/kg, respectively, and in Argissolo the responses of P. corethurus did not show a significant correlation for the increase of concentrations. The rejection tests had shown that, for low concentrations of the fungicide, the earthworms had prevented contaminated ground, confirming the high sensitivity of these organisms in detecting a decrease of concentrations in the ground. In Argissolo the responses of rejection of P. corethurus had not been significant according to the increase of concentrations of cooper. For a further evaluation of the risks of pesticides for tropical soils toxicity assays must be also carried out with a native species in order to verify its sensitivity in relation to the standard test species.
Keywords: ﻿; Ecotoxicologia; Agrotóxicos; Ambiente; Ecotoxicology, pesticides, environment; CIÊNCIAS AGRÁRIAS: AGRONOMIA